2019
DOI: 10.3389/fimmu.2019.02164
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Killer Cell Immunoglobulin-Like Receptors in Patients With Systemic Lupus Erythematosus Induce Natural Killer Cell Hyporesponsiveness

Abstract: Natural killer (NK) cell cytotoxicity toward self-cells is restrained by the inhibitory HLA class I-binding receptors CD94/NKG2A and the killer cell immunoglobulin-like receptors (KIRs). CD94/NKG2A and KIRs are also essential for NK cell education, which is a dynamic functional maturation process where a constitutive binding of inhibitory receptors to cognate HLA class I molecules is required for NK cells to maintain their full cytotoxic capacity. Previously, we described autoantibodies to CD94/NKG2A in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…A recent preprint suggests significant extrafollicular B cell activation with an excessive production of antibody-secreting cells (ASCs) in critically ill SARS-CoV-2 patients ( 34 ). This mechanism is highly similar to the development and progression of SLE, and these ASC might represent a possible source of the autoantibodies we report here ( 35 , 36 ). We do not assume that these autoantibodies were already present in predisposed patients prior to infection, because only two patients in our cohort had any clinical history of rheumatic or autoimmune disease.…”
Section: Discussionsupporting
confidence: 67%
“…A recent preprint suggests significant extrafollicular B cell activation with an excessive production of antibody-secreting cells (ASCs) in critically ill SARS-CoV-2 patients ( 34 ). This mechanism is highly similar to the development and progression of SLE, and these ASC might represent a possible source of the autoantibodies we report here ( 35 , 36 ). We do not assume that these autoantibodies were already present in predisposed patients prior to infection, because only two patients in our cohort had any clinical history of rheumatic or autoimmune disease.…”
Section: Discussionsupporting
confidence: 67%
“…Increasing experimental evidence has shown a direct involvement of NK cells and CD56 NK cell subsets in some human immunopathologies such as psoriatic arthritis, SLE, multiple sclerosis, and Behcet's disease [19,[23][24][25]. However, as innate lymphoid cells, the role and clinical significance of CD56 NK cell subsets in pSS patients are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SLE have a numerical deficit and a reduced cytotoxicity of NK cells. In addition, Sederberg et al, demonstrated that SLE patients may foster autoantibodies to both HLA class I-binding receptors (NKG2A, NKG2C), and multiple killer cell immunoglobulin-like receptors, which results in the dysregulation of self-nonself-recognition [ 22 , 25 ] ( Table 1 ).…”
Section: Unbalanced Immune Responses In Autoimmune and Systemic Comentioning
confidence: 99%
“…Similarly to familial HLH, patients with systemic juvenile idiopathic arthritis (sJIA) harbor mutations in genes related to NK cell cytotoxicity [ 58 , 59 ]. MAS also occurs in adult onset Still’s disease [ 60 ] and systemic lupus erythematosus (SLE) [ 25 ], where in the latter autoantibodies targeting CD94 + , result in an increase in NK cell cytokine secretion [ 22 ].…”
Section: Unbalanced Immune Responses In Autoimmune and Systemic Comentioning
confidence: 99%